Single-Fiber Bidirectional Optical Data Links with Monolithic Transceiver Chips. (27th February 2012) - Kern, Alexander; Paul, Sujoy; Wahl, Dietmar; Al-Samaneh, Ahmed; Michalzik, Rainer
Abstract : We report the monolithic integration, fabrication, and electrooptical properties of AlGaAs-GaAs-based transceiver (TRx) chips for 850 nm wavelength optical links with data rates of multiple Gbit/s. Using a single butt-coupled multimode fiber (MMF), low-cost bidirectional communication in half- and even full-duplex mode is demonstrated. Two design concepts are presented, based on a vertical-cavity surface-emitting laser (VCSEL) and a monolithically integrated p-doped-intrinsic-n-doped (PIN) or metal-semiconductor-metal (MSM) photodetector. Whereas the VCSEL-PIN photodiode (PD) chips are used for high-speed bidirectional data transmission over 62.5 and 50 μ m core diameter MMFs, MSM TRx chips are employed for 100 or 200 μ m large-area fibers. Such a monolithic transceiver design based on a well-established material system and avoiding the use of external fiber coupling optics is well suited for inexpensive and compact optical interconnects over distances of a few hundred meters. Standard MMF networks can thus be upgraded using high-speed VCSEL-PIN transceiver chips which are capable to handle data rates of up to 10 Gbit/s.